Problems of the Hierarchy of Needs Theory in the Perspective of Maqâshid al-Syarî‘ah - Jarman Arroisi; Amir Sahidin; Muhammad Fahmi Amrullah (Madania: Jurnal Kajian Keislaman, 2024)
Abraham Maslow's hierarchy of needs theory, which also discusses self-actualization, has been widely studied to increase meaning in various areas of life. However, there are many criticisms of the hierarchy theory, which automatically criticizes the concept of self-actualization. This criticism is increasingly visible when viewed with the Maqâshid al-syarî‘ah approach, which in its conception is highly concerned with the preservation of religion. Therefore, this article discussed the results of the critical study of Abraham Maslow's hierarchy of needs based on the Maqâshid al-syarî‘ah perspective. Based on library research with a critical analysis approach, it could be concluded that: first, Maslow's critical analysis of the hierarchy could be divided into two, namely criticism of hierarchy theory and the concept of self-actualization. Second, criticisms of Maslow's hierarchy theory included: the absence of religious elements in his theory and its irrelevance to the realities of people's lives. Third, criticism of Maslow's self-actualization included the absence of a clear definition of self-actualization. Furthermore, in practice, it led to an individual-materialistic attitude. Fourth, all these criticisms led to the Western humanist perspective, especially Abraham Maslow, who views humans as only mind, soul, and heart without any spirit or religion, which is the essence of Maqâshid al-syarî‘ah. Teori hirarki kebutuhan Abraham Maslow yang turut membicarakan aktualisasi diri banyak dikaji untuk meningkatkan kebermaknaan di berbagai bidang kehidupan. Namun demikian, terdapat banyak kritik terhadap teori hirarki tersebut, yang secara otomatis juga mengkritik konsep aktualisasi dirinya. Kritik tersebut semakin terlihat jika ditinjau dengan pendekatan Maqâshid al-Syarî‘ah yang dalam konsepsinya sangat perhatian terhadap penjagaan agama. Untuk itu, artikel ini akan membahas, telaah kritis hirarki kebutuhan Abraham Maslow perspektif Maqâshid al-syarî‘ah. Berdasarkan kajian berjenis library research dengan pendekatan analisis kritis dapat disimpulkan, pertama, telaah kritis hirarki Maslow dapat dibagi menjadi dua, yaitu kritik terhadap teori hirarki dan konsep aktualisasi dirinya. Kedua, kritik terhadap teori hirarki Maslow meliputi: ketiadaan unsur agama dalam teorinya dan ketidakrelevanan dengan realita kehidupan masyarakat. Ketiga, kritik terhadap aktualisasi diri Maslow, meliputi ketiadaan definisi yang jelas terkait aktualisasi diri, dan dalam prakteknya justru lebih mengarah kepada sikap individual-materialistik. Keempat, semua kritikan tersebut bermuara pada cara pandang Barat humanis, khususnya Abraham Maslow yang memandang manusia hanya sebatas akal, jiwa dan hati tanpa adanya ruh atau agama, yang merupakan inti dari Maqâshid al-syarî‘ah.